Boosting faculty engagement: the cultural and gender dynamics of gamification in universities - Silva Karkoulian (Cogent Education)
This study examines the impact of organizational culture on gamification and faculty engagement in Lebanese universities, guided by Flow Theory as the main theoretical framework. It particularly investigates the potential moderating effects of hierarchy, adhocracy, market, and clan cultures on the link between gamification and faculty engagement. The study additionally delves into how gender differs in these relationships. Using an online survey, 294 faculty members from Lebanese universities provided data, which SPSS v26 was utilized to analyze. The results show that market culture has a small but statistically significant moderating influence, whereas clan culture strongly moderates the relationship between gamification and faculty engagement. Gender analysis reveals that both clan and market cultures moderate this relationship for male faculty members, but not for females. These findings emphasize the importance of considering gender and organizational culture into account when developing gamification tactics to increase faculty participation. Hereafter, universities can leverage these insights to tailor effective gamification strategies. Future studies ought to examine these processes in a range of cultural and contextual contexts.